ARCHITECTURAL CONCEPTS FOR VALUE CHAINS - Janse van Rensburg, A.C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT:The Porter Value Chain has been widely adopted by the business community as a mechanism to understand and comprehend complexity in business environments, with the ultimate goal of structuring the business to maximize its competitive advantage. Implementing the Value Chain is not easy: a number of organizations can testify to their failure to derive any benefits at all from this concept. To overcome this problem, an approach is presented to assist the organization in creating a Value Chain reference model within the broader context of the organization